Effectiveness of progressive muscle relaxation and aromatherapy on fatigue in pregnant mothers - Kartilah, Tetet; Februanti, Sofia (Universitas Muhammadiyah Purwokerto, 2020)
Background: Fatigue in pregnant women can lead to cesarean delivery, also triggering problems during pregnancy, childbirth, and the puerperium. Therefore, there is a need for non-pharmacological interventions to reduce the level of fatigueObjective: This study aims to determine the effectiveness of giving progressive muscle relaxation (PMR) and aromatherapy to complaints of fatigue in pregnant womenMethods: This is a quasi-experiment with pretest and post-test with control group design. The sampling technique was simple random sampling, consisted of 52 respondents who were divided into two groups. The statistical using a paired t-test and independent t-testResults: After the administration of PMR and aromatherapy interventions, the fatigue score decreased significantly from 5.15 to 3.15; p<0.001. In the control group, the fatigue score was reduced from 5.04 to 4.00; p<0.0001. There was a significant difference in fatigue scores in the intervention and control groups (3.15 ± 1.592 vs. 4.00 ± 0.980; p<0.05).Conclusion: Combination progressive muscle relaxation exercises and aromatherapy are effective in reducing fatigue scores in pregnant women